2022
DOI: 10.1002/smll.202107371
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Understanding Lattice Silicon‐Controlled Catalytically Active Site Motifs from a Library of Transition Metal‐Silicon Intermetallics

Abstract: A joint theoretical and experimental study is reported to systematically explore over a library of transition metal‐silicon intermetallics for understanding silicon‐controlled active site motifs and discovering hydrogen‐evolving electrocatalysts. On the one hand, every low‐index surface termination of 115 transition metal (M)‐silicon (Si) intermetallics is enumerated, followed by cataloging of stable adsorption sites and prediction of catalytic activities on the main exposed facets. It is theoretically found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Many other metals/metalloids in the p-block group easily form structurally ordered intermetallics with transition metals. [84][85][86] Our group theoretically studied a series of intermetallics of RuX (X = Si, Ge, Sn, Al, Ga and In). 87 We found that the activity of these Ru top sites was closely related to the d-band center (Fig.…”
Section: Intermetallic Catalystsmentioning
confidence: 99%
“…Many other metals/metalloids in the p-block group easily form structurally ordered intermetallics with transition metals. [84][85][86] Our group theoretically studied a series of intermetallics of RuX (X = Si, Ge, Sn, Al, Ga and In). 87 We found that the activity of these Ru top sites was closely related to the d-band center (Fig.…”
Section: Intermetallic Catalystsmentioning
confidence: 99%
“…The reduction of metallic Fe and Mn promotes the reduction of Si, because these metals reduce the activity and activity coefficient of Si within the alloy and facilitate the formation of silicides, thereby impacting the reduction process. The affinity of Si for forming silicides with metals in the ferroalloy follows the sequence Mn > Fe > Cr, based on the standard change in Gibbs free energy associated with the formation of the respective silicides [17,18]. Cr, by dissolving up to 70% Mn in the solid state, reduces Mn's activity and enhances the reduction process [2].…”
Section: Thermodynamic Modellingmentioning
confidence: 99%
“…Silicon oxides are commonly considered as passive layers in electrocatalytic systems, but their stability also suggests their potential as support materials. 100 In addition, the SiO 2 support may also catalytically induce loading processes. 101 In general, silicon oxides and tin oxides have similar insolubility and chemical inertness properties.…”
Section: Metal Oxides As Support Materialsmentioning
confidence: 99%